Integrated use of manure and fertilizers increases rice yield, nutrient uptake and soil fertility in the boro-fallow-t.aman rice cropping pattern (SAARC Journal of Agriculture, 2018)
The effect of integrated use of manure and fertilizers on crop yield, nutrient uptake and soil fertility was studied in the Boro-fallow-T. Aman cropping pattern over two years. The experiment was set up at Bangladesh Agricultural University (BAU) farm, Mymensingh under the AEZ 9 (Old Brahmaputra Floodplain). The field trial consisted of eight treatments and control (no fertilizer or manure), 100% chemical fertilizers (CF), and IPNS based six treatments with six types of manure. Cowdung (CD), CD slurry, Trichocompost (TC) and vermicompost (VC) were added to soil at 5 t ha-1 and poultry manure (PM) and PM slurry applied at 3 t ha-1. For all IPNS treatments, nutrient supply from manure was adjusted with that from chemical fertilizers. In each crop cycle, manure was applied to the first crop (Boro rice) and the residual effect was evaluated on the succeeding crop (T.Aman rice). The IPNS based treatments significantly increased the grain and straw yields of Boro rice and it had also positive residual effect on T.Aman rice. Trichocompost and vermicompost, among the six IPNS treatments, demonstrated higher crop yield and that was followed by poultry manure slurry and cowdung slurry. Integrated use of manure with fertilizers gave on an average 8.3-33.8% and 2.9-18.3% higher grain yield in Boro and T. Aman rice, respectively over sole fertilizers treatment. Higher nutrient uptake by crops (N, P, K & S) was also observed in IPNS treated plots. The IPNS treatments improved soil fertility in terms of increasing organic matter, N, P and S contents of soil after two crop cycles. The study suggests that manure and fertilizers should be used in an integrated manner to achieve sustainable crop yield, without incurring loss to soil fertility.SAARC J. Agri., 15(2): 147-161 (2017)